Study some effective Factors on work fluoride selective Electrode (Latakia University Journal -Basic Sciences Series, 2018)
This research studied the effect of concentration electrolyte (its volume and concentration) and PH on analytical conditions (concentration; slope Nernsty ) and technical conditions were ( time stability ; time response ; speed response) on used  fluoride selective Electrode all mesurements measured at degree lab temperature(25CO). using for this aim five salt as electrolyte : KI ;  KCl ; (NH4)2SO4 ; NaCl ; NH4Cl .  for choose best conditions analytical  and technical conditions. KCl salt found with concentration 2.5 M and its volume    1.25 ml . time stability 1 min ; time response 7.33 sec; speed response 1 sec and R2=0.9989  then studied PH effect on electrode work using HCl and independently CH3COOH found in best range PH (5.0 – 6.0) using CH3COOH and its salt (CH3COONa) and buffer concentration CH3COOH = 0.244 ; CH3COONa=  0.756 M.  Best volume from buffer  1.5ml and the work range of buffer PH (3.25 – 8.0(  for concentration5-10×23.1 M and characterized accuracy and was rang Standard Deviation SD= (0.925-0.280) and  rang Relative Standard Deviation RSD%=(1.19 – 4.18) and ran Retrospective  % 103.0-% 95.6.